KEKERASAN TERHADAP ANAK DALAM PERSPEKTIF PENDIDIKAN - Krisbiyantoro, Jujuk; Lestari, Puji (Forum Ilmu Sosial, 2008)
Indonesia had ratification Covention o the Right of the Child since 5th September 1990. It constitutesIndonesia commitment in respect ad pock right for child. This commitment most decants in constitution1945 sections 28 b (2), and it’s operational on Number Law 23 year 2002 about protection child. Itcommands the school as education institution to be aware to the pupils of the violance by its school andthe environtment. The conservatives point of view, reminding that school has the fuctions of handlingthe proses of studies based on the values, sciense and the general norms, as well as its functions of socialcontrol.Keywords: Children,child abuse, education